2019
DOI: 10.1016/j.hrthm.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch pacing for symptomatic bradycardia: Implant success rate, safety, and pacing characteristics

Abstract: BACKGROUND In patients with or without left bundle branch block, left bundle branch pacing (LBBP) can produce near normalization of QRS duration (QRSd). This has recently emerged as an alternative technique to His bundle pacing.OBJECTIVES The purpose of this study was to characterize a novel approach for LBBP in patients with bradycardia indications for pacing and to assess implant success rate and midterm safety.METHODS Patients with bradycardia indications for pacing underwent LBBP by a trans-ventricular-sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
177
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 31 publications
19
177
1
2
Order By: Relevance
“…LBBP is defined as follows: (a) a paced QRS morphology on 12‐lead electrocardiogram (ECG) shows the pattern of right bundle branch conduction delay (RBBD) or improving the LBB conduction in patients with LBBB; (b) a left bundle branch potential can be recorded; and (c) a fast peak left ventricular activation time (LVAT) in V5/V6 on the surface 12‐lead ECG is present. The paced (QRSd) is usually less than 120 ms according to our study in patients with bradycardia (N = 70) …”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…LBBP is defined as follows: (a) a paced QRS morphology on 12‐lead electrocardiogram (ECG) shows the pattern of right bundle branch conduction delay (RBBD) or improving the LBB conduction in patients with LBBB; (b) a left bundle branch potential can be recorded; and (c) a fast peak left ventricular activation time (LVAT) in V5/V6 on the surface 12‐lead ECG is present. The paced (QRSd) is usually less than 120 ms according to our study in patients with bradycardia (N = 70) …”
Section: Introductionmentioning
confidence: 83%
“…Our previous study demonstrated the procedural and clinical feasibility of LBBP via a transventricular‐septal approach . Subsequently, we reported the success rate, safety, and 3‐month follow‐up outcomes of LBBP . With further investigations showing a similar effect of LBBP when compared with HBP, more electrophysiologists have begun to practice this technique.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations